Paradigm Shift from Physical Market to Virtual Market - Swikriti Verma (Journal of Advanced Research in HR and Organizational Management, 2020)
In this day and age, web based business has obtained significance. India has been encountering huge development in online business, with numerous little organizations mushrooming and a couple of goliaths endeavoring to assume control over the enormous Indian internet business market. Flipkart, Amazon, Snapdeal, Uber, Ola, and so on are a couple of models. Some of them are supposed to be local, as in their advertisers have been Indians. Be that as it may, later they pulled in unfamiliar value, and at last are overwhelmed by unfamiliar financial backers